Diagnostic Usefulness of Real-Time Elastography for Liver Fibrosis in Chronic Viral Hepatitis B and C. (10th August 2014) - Kim, Young Woon; Kwon, Jung Hyun; Jang, Jeong Won; Kim, Min Ju; Oh, Byong Sun; Chung, Kyu Won; Park, Eun Su; Nam, Soon Woo
Abstract : The aim of this study was to investigate the diagnostic usefulness of real-time elastography (RTE) for liver fibrosis in chronic viral hepatitis B (CHB) and C (CHC). Fifty-one and thirty-two of the patients were diagnosed with CHB and CHC, respectively. Enrolled patients underwent liver biopsy and RTE. The FIB-4 index and aspartate transaminase-to-platelet ratio index (APRI) were also measured. The liver fibrosis index (LFI) by RTE increased significantly with the Knodell fibrosis stage: 3.14 ± 0.62 for F0, 3.28  ±  0.42 for F1, 3.43  ±  0.53 for F3, and 4.09  ±  1.03 for F4 (P = 0.000 ). LFI as well as APRI, FIB-4, platelet, albumin, and prothrombin time showed the difference in patients with advanced fibrosis (≥ F3) and those with mild fibrosis (≤ F1). In addition, RTE had better discrimination power between ≥ F3 and F4 than between FIB-4 and APRI. In CHC patients, the area under receiver operating characteristic curves of RTE for advanced fibrosis was higher than that in CHB patients (0.795 versus 0.641). RTE is useful for the assessment of advanced fibrosis in patients with CHB and CHC and has better discrimination power than other serologic markers.